Experimental monitoring and computer simulation of a solar air-conditioning system - Rao, Malla Raghava; Reddy, T. A.; Exell, Robert H.B.; Huynh, Ngoc Phien; Canadian International Development Authority (Bangkok : Asian Institute of Technology, 1985)
The actual performance of a 2 ton YAZAKI WFC600S solar absorption air-conditioning system was monitored by setting up the necessary instrumentation and recording the data on cassette tapes using two Campbell CR21 microloggers . Programs were written to retrieve and process this recorded raw data which was then analyzed in order to study the system performance. Conclusions are drawn and recommendations made in order to ameliorate the system performance . It has been observed that the chiller is very much undersized for the intended load and also that there could be an improvement of system performance by minor variations in control and operational strategy. A detailed simulation program was also developed which models the radiation, collector system, building load a nd the chiller unit while accounting for hysteresis and cycling effects . The simulation assumes a quasi steady state over a 5 minute simulation time step. The simulation program was validated with measured data over a few days. In order to determine the long term performance of the system , the program was run for the entire year and a value of 34.3% f or the annual solar fraction was obtained. Programs were developed in order to simulate the system performance using simplified simulation methods like the o-f Chart, TMD and MIRA methods. These resulted in annual solar fractions of 0. 3500, 0.4163 and 0.3562 respectively which are in accordance wit h the detailed simulations indicating the validity of these procedures to air-conditioning systems and also that a high amount of accuracy is achievable by a judicious choice o f an appropriate s1mplitied design method. This procedure would save a lot of resources on program development and computing time.
A thesis submitted in partial fulfillment of requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1985
Keywords: Solar air conditioning -- Simulation methods